Peran UMKM Dalam Pembangunan Dan Kesejahteraan Masyarakat Kelurahan Desa Saringembat, Kabupaten Tuban - Citra Nia Ramadhani; Maharani Ikaningtyas (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
MSMEs (Micro, Small, and Medium Enterprises) play a significant role in supporting economic development and improving community welfare, especially in rural areas like Saringembat Village, Tuban Regency. This community service aims to empower local MSMEs through skill training, enhancing market access, and utilizing simple technologies to help them grow their businesses. The activities involve direct assistance to MSME actors in the fields of crafts, culinary arts, and local agriculture. The outcomes of these activities demonstrate increased income, business growth, and active community participation in strengthening the local economy. Digitalization, including marketing and business management processes, has also been initiated to help MSMEs become more competitive in the current era. Improving community welfare through this development is expected to contribute directly to sustainable development in Saringembat Village.